2014
DOI: 10.1017/s1751731114001190
|View full text |Cite
|
Sign up to set email alerts
|

Animal behavior and pasture depletion in a pasture-based automatic milking system

Abstract: In pasture-based automatic milking systems (AMS), feed is the main incentive that can be managed to encourage reliable and consistent voluntary and distributed cow traffic. Modifying timing, placement and size of feed allocations is expected to have an effect on cow behavior that could avoid the occurrence of extended milking intervals, which have a negative effect on milk yield. Therefore, behavioral studies provide information on how cows modify their actions under different management regimes and can help e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…The average milking interval of 14·4 h in our current study was similar to the milking intervals for pasture based AMS systems, albeit higher than that on a pastoral based research farm (Jago & Burke, 2013), and higher than those reported for indoor-based AMS by Lyons et al (2014). This implied that the AMS farms in the current study had a representative range for milking intervals occurring in commercial practice.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The average milking interval of 14·4 h in our current study was similar to the milking intervals for pasture based AMS systems, albeit higher than that on a pastoral based research farm (Jago & Burke, 2013), and higher than those reported for indoor-based AMS by Lyons et al (2014). This implied that the AMS farms in the current study had a representative range for milking intervals occurring in commercial practice.…”
Section: Discussionsupporting
confidence: 82%
“…In fact, the ICAR protocols have been developed based on studies conducted in AMS systems where cows are housed (ICAR, 2016). While a 16 h sampling period (suggested by Hand et al 2006) may be appropriate in systems with higher milking frequencies, it may not be suitable for pasture based systems since in a review on AMS systems, Lyons et al (2014) reported that cows on pasture based AMS farms have lower milking frequencies than indoor fed cows that are milked by AMS. It is, thus, important to understand the impact of the lower milking frequencies on the accuracies of the sampling protocol for herd testing.…”
mentioning
confidence: 99%
“…Studies measuring the actual time at pasture are needed to further investigate the effect of the length of the grazing period on claw health. In AMS, where cows are supposed to walk to pasture voluntarily, cow traffic and grazing have to be further developed (Sporndly and Wredle, 2004;Lyons et al, 2014).…”
Section: Grazing Factorsmentioning
confidence: 99%
“…The motivation of cows to graze when given a free choice is dependent on different factors (Charlton et al, 2013;Lyons et al, 2014). In a Canadian preference study, dairy cows in a conventional freestall system chose being out at night but to a lesser extent in rainy weather and chose to be inside during the day and to a greater extent with increased outdoor temperature and humidity (Legrand et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In these conditions, low pasture biomass was linked to an increase in time spent indoors and consequently to a rise in milkings. Lyons et al (2014) observed that at low pasture availability, cows tend to walk to a new pasture allocation. A similar observation was made in the present study, as cows preferred to return to the robot and eventually get refused than to stay on the pasture.…”
Section: Impact On Voluntary Cow Trafficmentioning
confidence: 99%